Reflective habitus and crises of the field: status quo vs reform in Muhammadiyah in post-1998 Indonesia - Christian (Curtin University, 2013)
This dissertation aims to explain how support for both maintaining the status quo and promoting reform emerged in post-1998 Muhammadiyah, and what caused these tendencies to emerge. To do this, I employ Pierre Bourdieu’s concepts of habitus, field and crisis, and use the methods of content analysis and active interview. I conclude by arguing that these two opposite tendencies emerge from the same reflective predisposition, and are responses to two different perceptions of the West.